Kajian Persepsi Kontraktor Terhadap Strategi Meningkatkan Penggunaan Agregat Kitar Semula, Plastik dan Kaca dalam Pembinaan - Lee, Wen Xiang; Seow, Ta Wee (Research in Management of Technology and Business, 2024)
Construction waste is a serious issue and has a detrimental effect on the project, society, and the environment. Sustainable development is increased and construction waste can be produced. The objectives of this study are to examine the contractor’s views on the use of recycled aggregates, plastic and glass, identify factors cause recycled aggregates, plastic and glass less used and propose strategies to increase the use of recycled aggregates, plastic and glass. The methodology is quantitative methods, questionnaires and data collected analyzed for research objectives. The results of the study show that 57.4%, 53.2% and 61.7% agree for each objective. The proposal is establish guidelines and quality assurance and modern recycling technology.